Product-conformation-driven ligation of peptides by V8 protease - Srinivasulu, Sonati (Cold Spring Harbor Laboratory Press, 2002)
Organic co-solvent-induced secondary conformation of α(17–40) of human hemoglobin facilitates the splicing of E(30)-R(31) in a mixture of its complementary segments by V8 protease. The amino acid sequence of α(17–40) has been conceptualized by the general structure FR(I)-EALER-FR(II) and the pentapeptide sequence EALER playing a major role in inducing the α-helical conformation. The primary structure of α(17–40) has been engineered in multiple ways to perturb one, two, or all three regions and the influence of the organic co-solvent-induced conformation and the concomitant resistance of E(30)-R(31) peptide bond to V8 protease digestion has been investigated. The central pentapeptide (EALER), referred to here as splicedon, appears to dictate a primary role in facilitating the splicing reaction. When the same flanking regions are used, (1) splicedons that carry amino acid residues of low α-helical potential, for example G at position 2 or 3 of the splicedon, generate a conformational trap of very low thermodynamic stability, giving an equilibrium yield of only 3%–5%; (2) splicedons with amino acid residues of good α-helical potential generate a conformational trap of medium thermodynamic stability and give an equilibrium yield of 20%–25%; (3) the splicedons with amino residues of good α-helical potential and also an amino acid that can generate an i, i + 4 side-chain carboxylate-guanidino (amino) interaction, a conformational trap of maximum thermodynamic stability is generated, giving an equilibrium yield of 45%–50%; and (4) the thermodynamic stability of the conformational trap of the spliced peptide is also influenced by the amino acid composition of the flanking regions. The V8 protease resistance of the spliced peptide bond is not a direct correlate of the amount of α-helical conformation induced into the product. The results of this study reflect the unique role of the splicedon in translating the organic co-solvent-induced product conformation as a site-specific stabilization of the spliced peptide bond. It is speculated that the splicedon with higher α-helical potential as compared to either one of the flanking regions achieves this by integrating its potential with that of the flanking region(s). Exchange of flanking regions with the products of other V8 protease–catalyzed splicing reactions will help to establish the general primary structural requirements of this class of splicing reactions and facilitate their application in modular construction of proteins.